New records, a synonymy and a new species of Aradus Fabricius, 1803 (Hemiptera: Heteroptera: Aradidae) from China - Bai, X.; Heiss, E.; Cai, W. (Zootaxa, 2010)
In this paper five new records for the Chinese flat bug fauna are reported: Aradus angularis Sahlberg 1886, Aradus betulae (Linnaeus 1758), Aradus distinctus Fieber 1860, Aradus tonkinensis Kormilev & Heiss 1976, and Aradus rysakovi Kiritshenko 1951. Aradus wuzhisanensis Liu 1981from Hainan Province is synonymised with Aradus candidatus Bergroth 1889, a species known from Myanmar, Thailand, and Laos. A new species, Aradus gaoligongensis n. sp. from Sichuan Province, belongs to the “transiens”-group and is described and figured. In addition, new distribution data are given for 8 Aradus species.